2022
DOI: 10.1055/s-0042-1755587
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity among Adolescents: A School-Based Preliminary Cross-Sectional Study

Abstract: Introduction Globally, the magnitude of overweight and obesity is alarmingly high. In recent years, there are increased opportunities for adolescents to become overweight due to their sedentary lifestyles. Obesity is a chronic, noncommunicable, and lifestyle diseases resulting from energy imbalance. On evidence, overweight and obesity are still preventable as primordial prevention. Thus, knowing the prevalence will help us to plan prevention strategies. Objectives The objective of the study was to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the present study, the prevalence was significantly maximum among those who had sedentary lifestyles, i.e., watched television for more than 2 hrs/day (40.9%). Mathew et al [24] reported that screen time was a significant factor associated with overweight and obesity. In the present study, the odds ratio of late adolescence, higher socioeconomic class, more consumption of fast food, carbonated drinks, physical inactivity, and sedentary behavior showed a strong association with the prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the prevalence was significantly maximum among those who had sedentary lifestyles, i.e., watched television for more than 2 hrs/day (40.9%). Mathew et al [24] reported that screen time was a significant factor associated with overweight and obesity. In the present study, the odds ratio of late adolescence, higher socioeconomic class, more consumption of fast food, carbonated drinks, physical inactivity, and sedentary behavior showed a strong association with the prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%